2005
DOI: 10.1111/j.1460-9592.2005.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline poisoning in a 2‐year old

Abstract: We describe a case of a 2-year-old boy who ingested 35 mg.kg(-1) of amitriptyline. He developed central nervous system toxicity, as demonstrated by coma and seizures and cardiac toxicity (cardiac arrest) within 1 h of ingestion. The cardiac toxicity was refractory to standard therapy. His cardiac rhythm alternated between ventricular tachycardia and pulseless ventricular tachycardia/ventricular fibrillation for a period of 17 h. Following prolonged cardiopulmonary resuscitation and aggressive supportive manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…These cases were described in a retrospective study included 44 cases of AMI intoxication [8]. A non-lethal case of a 2-year-old boy who ingested 35 mg/kg À1 of AMI was also reported [9]. These articles specified the dose ingested but not the serum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were described in a retrospective study included 44 cases of AMI intoxication [8]. A non-lethal case of a 2-year-old boy who ingested 35 mg/kg À1 of AMI was also reported [9]. These articles specified the dose ingested but not the serum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 3 , 13 , 14 Blockage of cardiac sodium and potassium channels may result in cardiac conduction delay, dysrhythmia and hypotension due to myocardial depression. 1 , 2 , 4 , 14 This process may appear on the ECG as prolonged PR, QRS and QT times, sinus tachycardia, and supraventricular and ventricular arrhythmias. 1 , 11 The most important cause of death is persistent hypotension resulting from myocardial depression due to arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been used to treat patients with severe cardiotoxicity due to amitriptyline overdose. These include serum alkalinisation with hypertonic NaHCO 3 20 or hyperventilation, 21 inotropic agents, 4 , 22 magnesium sulphate, 5 anti-arrhythmic drugs, 2 , 14 glucagon 12 haemoperfusion, 23 , 24 or lipid emulsion. 25 Although many studies have compared these treatment methods, no treatment has been shown to prevent or reduce the toxicity in patients who may potentially develop severe toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[34] For amitriptyline serious toxicity dose varies between 10 and 30 mg/kg in adults. [56] Ash et al . [7] reported that the lethal dose can be variable and ingestion of more than 1 g TCA or a blood level of 1.000 mg/l predicts a high risk of mortality.…”
Section: Discussionmentioning
confidence: 99%